A Ordem dos Médicos e a condição do trabalho médico na Estado Novo - Costa, Rui Manuel Pinto da (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The promotion and defence of the professional classes have been associated with institutions which congregate the common interests of their members. In the case of the contemporary medical class, it was in the context of the Medical Association (Ordem dos Médicos) that these professionals publicised and discussed the promotion of their class before the ruling political power. In this essay, one addresses the trajectory of this institution, the efforts it developed and its more significant moments in the political context of Portugal’s New State. One emphasised mainly the process established by the Association which aimed at setting up the legitimacy of the class to perform the duties of supremacy and control within the national health system. At the same time, one stressed the role played by Miller Guerra, analysed as an outstanding actor in this context of revendication and promotion of medical power.